Hemmnisanalyse für den dynamisierten Ausbau der Vergärung kommunalen Bioguts-Bio-DYN. - Kern, Michael; Raussen, Thomas; Sprick, Werner; Turk, Thomas (schmidt, 2019)
In 41 Interviews mit kommunalen Entscheidungsträgern wurde deren Diskussions- und Entscheidungsprozess mit dem Fokus auf die Hemmnisse bezüglich der Biogutvergärung (Gewichtung von Pro- und Contra-Argumenten) untersucht. Die Erhebung anlagenbezogener Betriebsdaten bei 20 Betreibern von Vergärungsanlagen und deren Bewertung war ein weiterer Schwerpunkt. Abschließend wurden Einschätzungen der Studienteilnehmer zu zukünftigen Rahmenbedingungen für die Vergärung sowie Empfehlungen an die politischen Entscheidungsträger auf Landes- und Bundesebene erhoben.

In 41 interviews with municipal decision-makers, their discussion and decision-making processes were examined with a focus on the obstacles to biogas fermentation. Essentially, legislative obstacles with regard to funding, fertiliser legislation and discussions on TA Luft were cited. In the first place a lack of economic viability of fermentation is feared, which could not be confirmed in an analysis of the real treatment costs. Overall, the satisfaction of the operators of biogas fermentation plants is high; the vast majority of them would opt for this again from today s perspective. Against the background of stricter requirements with regard to energy and fermentation residue marketing and structural plant equipment, the study participants see the operators facing major challenges and are very sceptical. The concrete recommendations of the study participants are addressed above all to political decision-makers in particular on federal level.
Keywords: Entsorgung; Bioabfall; Vergärung; Bewertung